Comparative Analysis of Molecular Structure, Function and Expression of Buffalo (Bubalus bubalis) Toll-Like Receptor 9 - Manuja, Anju; Manuja, Balvinder K.; Kataria, Ranjit S.; Sethi, Ramesh K.; Singh, Raj K. (Journal of Buffalo Science, 2013)
Toll-like receptor 9 (TLR9) has been characterized as a receptor that recognizes unmethylated CpG motif and triggers a pro-inflammatory cytokine response that influences both innate and adaptive immunity. Buffalo is an economically important livestock species in many Asian and Mediterranean countries, but there is little information available on its TLR9 structure and response to stimulation with its agonist CpG-ODNs. Hence in this study, we report the analysis of newly sequenced buffalo TLR9 gene fragment. In this study, buffalo TLR9 amino acid sequence revealed close association of TLR9 proteins within other bovines and small ruminants; but high divergence from other species. Multiple alignment of deduced amino acid sequence of Bubalus bubalis TLR9 with other species showed that 156/201 (74.28%) amino acids were conserved in all species. Leucine rich repeat (LRR) motifs in the ectodomain of TLR9 are responsible for molecular recognition of its agonist. The LRR pattern of Bubalus bubalis TLR9 protein was predicted towards N-terminal sequence and was found to be conserved among all species except Rattus norvegicus and Equus caballus. Blast analysis of buffalo TLR9 sequence with single nucleotide polymorphisms (SNPs) database revealed 13 SNPs out of which 7 were cds-synonymous and 6 were of the functional significance. Furthermore, kinetics of TLR9 and proinflammatory IL-1β and TNF-α cytokine expression by buffalo PBMCs influenced by CpG-ODN is also discussed.